Anatomic Morphometrics of the "Senene" Tettigoniid Ruspolia differens Serville (Orthoptera: Conocephalidae) from North-West Tanzania. (28th January 2013) - Matojo, Nicodemus D.; Yarro, Jacob G.
Abstract : The morphometrics of Ruspolia differens (order: Orthoptera; family: Conocephalidae), the longhorn grasshopper that is widely known as senene by its Kiswahili name, was largely unclear although the species serves broadly as a delicacy relish snack. In this study, the anatomic morphometrics of this insect was critically inferred based on the samples that were collected from North-west Tanzania in April-May 2009. R. differens was revealed to have a number of unique anatomic features that can essentially serve in its diagnosis. These include the paired male metathoracic flaps, finger-like prosternal protuberances, hind femoral spines, subequal tibial black markings, and an obvious male biased antennal dimorphism.